Engineered Nanomaterials - Health and Safety 2020
DOI: 10.5772/intechopen.90717
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Impact of Green Synthesized Silver Nanoparticles

Abstract: Toxicity and biocompatibility of silver nanoparticles are of a major concern due to their extensive production regardless of their application in current industries. Information about toxicology or biocompatibility is crucial regarding their proper utilization and application in clinical as well as environmental aspect. This chapter describes in detail about the different techniques and technology of synthesis of silver nanoparticles and explains their different physiochemical properties in context of the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The previously documented reports have also mentioned the SPR peak of AgNPs in a range of 400–500 nm. 55 Further, the hydrodynamic size and stability of G-AgNPs and C-AgNPs were determined in the different media used for further toxicological assays. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The previously documented reports have also mentioned the SPR peak of AgNPs in a range of 400–500 nm. 55 Further, the hydrodynamic size and stability of G-AgNPs and C-AgNPs were determined in the different media used for further toxicological assays. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have been reported that can act as bio-reducing and capping agents during the biogenic synthesis of nanoparticles [26][27][28] . The synthesis of silver nanoparticles through a bioreduction method allows clean, non-toxic, and environmentally friendly synthesis, others that promotes the obtaining of nanoparticles with less cytotoxicity 29,30 . Silver nanoparticles(AgNPs) was obtained by bio-reduction of Ag +1 ions with phenolic compounds of the exine, furthermore pollen grains serves as a bio-template since promotes the adhesion of silver nanoparticles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ROS reactive oxygen species regulation, apoptosis, and necrosis. In view of these reports, the in vivo toxicity can be described as an effect of dysregulated expression of ROS production, leading to greater apoptosis and other cell death-related phenomena (Patel et al, 2019;Verma et al, 2019).…”
Section: Metal and Metal Oxide Nanoparticle-based Toxicity Profiling mentioning
confidence: 99%